A roadmap investment strategy to reduce carbon intensive refrigerants in the food retail industry. (1st December 2020) - Hart, Matthew; Austin, William; Acha, Salvador; Le Brun, Niccolo; Markides, Christos N.; Shah, Nilay
Abstract: High global warming potential (GWP) refrigerant leakage is the second-highest source of carbon emissions across UK supermarket retailers and a major concern for commercial organisations. Recent stringent UN and EU regulations promoting lower GWP refrigerants have been ratified to tackle the high carbon footprint of current refrigerants. This paper introduces a data-driven modelling framework for optimal investment strategies supporting the food retail industry to transition from hydrofluorocarbon (HFC) refrigeration systems to lower GWP systems by 2030, in line with EU legislation. Representative data from a UK food retailer is applied in a mixed integer linear model, making simultaneous investment decisions across the property estate. The model considers refrigeration-system age, capacity, refrigerant type, leakage and past performance relative to peer systems in the rest of the estate. This study proposes two possible actions for high GWP HFC refrigeration systems: a) complying with legislation by retrofitting with an HFO blend ( e.g . R449-A) or b) installing a new natural refrigerant system ( e.g. R744). Findings indicate that a standard ( i.e. business-as-usual) investment level of £6 m/yr drives a retrofitting strategy enabling significant reduction in annual carbon emissions of 71% by the end of 2030 (against the 2018 baseline), along with meeting regulatory compliance. The strategy is also highly effective at reducing emissions in the short term as total emissions during the 12-year programme are 59% lower than would have been experienced if the HFC emissions continued unabated. However, this spending level leaves the business at significant risk of refrigeration system failures as necessary investments in new systems are delayed resulting in an ageing, poorly performing estate. The model is further tested under different budget and policy scenarios and the financial, environmental, and business-risk implications are analysed. For example, under a more aggressive investment approach of £50 m/yr carbon reductions are at 93% by the end of 2030, whilst also ensuring compliance with the legislative cut-off four years early in 2026 and substantially enhancing the reliability of the refrigeration systems in the portfolio. Alternatively, when emissions are minimised instead of cost with a £50 m/yr investment level, 99% decarbonisation is achieved by 2030. Overall, the study highlights the trade-offs between capital investment and system resilience requiring a careful balance of priorities and the need to have up to date information so decision makers can reliably drive a successful strategy towards more sustainable operation of refrigeration systems. Graphical abstract: Image 1 Highlights: Novel optimisation model to reduce F-gas emissions in the food retail industry. Retrofitting R-449A or R-744 systems considered to comply with regulations. HFC tax does not significantly curtail emissions as current policy is effective. Under current investment levels (£6 m/yr) a 71% CO2e reduction is achieved by 2030. If investments are frontloaded (£50 m/yr) a 99% reduction is feasible by 2030.